2013
DOI: 10.2174/1874230001307010001
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Demand Varies During a Blind Navigation Pathway In Young And Older Adults

Abstract: This study sought to investigate the attentional demands while performing a blind navigation task in young and elderly subjects. Fourteen subjects of age 20 to 32 years and 10 subjects of age 62 to 80 years participated in the experience. Blinded navigation task consisted of visually identifying and then walking blindly towards a target 8 meters ahead. To measure attentional demands during navigating, participants were asked to respond to auditory signals by saying "top" as quickly as possible without altering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This line of work also suggests that when environmental distractions related to the path, such as the complexity of the space or number of turns on the path, yield the opposite pattern whereby the distance traveled is overestimated. It has also been demonstrated that when walking to a landmark location without vision, the ability to perform a secondary task is particularly impacted when very near the landmark location, but relatively unimpaired when farther from objects (Lajoie, Paquet, & Lafleur, 2013). Future work using our spatial learning paradigm could include distance estimations to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…This line of work also suggests that when environmental distractions related to the path, such as the complexity of the space or number of turns on the path, yield the opposite pattern whereby the distance traveled is overestimated. It has also been demonstrated that when walking to a landmark location without vision, the ability to perform a secondary task is particularly impacted when very near the landmark location, but relatively unimpaired when farther from objects (Lajoie, Paquet, & Lafleur, 2013). Future work using our spatial learning paradigm could include distance estimations to address this question.…”
Section: Discussionmentioning
confidence: 99%